The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/cc12821
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of noninvasive ventilation in patients with blunt chest trauma: a systematic review

Abstract: IntroductionThis systematic review looks at the use of noninvasive ventilation (NIV), inclusive of noninvasive positive pressure ventilation (NPPV) and continuous positive pressure ventilation (CPAP), in patients with chest trauma to determine its safety and clinical efficacy in patients with blunt chest trauma who are at high risk of acute lung injury (ALI) and respiratory failure.MethodsWe searched the MEDLINE, EMBASE and Cochrane Central Register of Controlled Trials (CENTRAL) databases. Pairs of reviewers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 24 publications
3
42
0
8
Order By: Relevance
“…Four patients in the CPAP-ventilation group (26.7%) and three patients in the BiPAP group (20%) required endotracheal intubation, so the success rate to avoid intubation was 73.3% in the CPAP group and 80% in the BiPAP group (Table 4), this agrees with the finding of Duggal et al 2013 [20]. The reasons for intubation ( Table 5) were failure of noninvasive ventilation to maintain the PaO 2 above 60 mmHg (four patients), its inability to correct dyspnea (two patients) and hemo-dynamic instability (one patient).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Four patients in the CPAP-ventilation group (26.7%) and three patients in the BiPAP group (20%) required endotracheal intubation, so the success rate to avoid intubation was 73.3% in the CPAP group and 80% in the BiPAP group (Table 4), this agrees with the finding of Duggal et al 2013 [20]. The reasons for intubation ( Table 5) were failure of noninvasive ventilation to maintain the PaO 2 above 60 mmHg (four patients), its inability to correct dyspnea (two patients) and hemo-dynamic instability (one patient).…”
Section: Discussionsupporting
confidence: 93%
“…Nosocomial pneumonia and pneumo-thorax were the most commonly reported adverse events associated with NIV use in previous studies, and the rate ranged from 8% to 13.8% [20,21]. The rate of pneumothorax reported in two studies ranged from 5.5% to 24% [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…17 Another review reported that blunt chest trauma subjects benefited from early initiation of NIV, leading to decreased ICU stay, complications, and mortality. 16 Nevertheless, neither of these studies included HFNC, even though some literature has proposed that HFNC is equivalent or superior to standard NIV. 4,12 If HFNC performs similarly to, or even better than, standard NIV devices, HFNC therapy may have analogous benefits to medical and trauma patients who were found in the aforementioned studies using NIV.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] HFNC has been used successfully with medical ICU patients, as well as in postoperative cardiac and vascular populations. 3,6,[10][11][12][13][14][15] One study in the trauma literature supported use of early noninvasive ventilation (NIV) in blunt trauma, 16 but much work is yet to be done regarding use of HFNC in trauma populations.…”
Section: Introductionmentioning
confidence: 99%
“…The use of NIV is contraindicated in cases of non-drained pneumothorax. [23][24][25][26][27] -It is strongly recommended that the physiotherapist review the imaging exams (CT scans and/or x-rays) before attending them and discuss them with the medical staff.…”
Section: Chest Traumamentioning
confidence: 99%